Validation of self-reported sleep against actigraphy - Girschik, J.; Fritschi, Lin; Heyworth, J.; Waters, F. (British Medical Journal Group, 2012)
Background: Self-report remains the most practical and cost-effective method for epidemiologic sleep studies involving large population-based samples. Several validated questionnaires have been developed to assess sleep, but these tools are lengthy to administer and may be impractical for epidemiologic studies. We examined whether a 3-item sleep questionnaire, similar to those typically used in epidemiologic studies, closely corresponded with objective measures of sleep as assessed using actigraphy monitoring. Methods: Eligible participants were Western Australian women aged 18 to 80 years. Participants completed a sleep questionnaire, wore a wrist actigraph for 7 nights, and completed a brief daily sleep log. Objective actigraphy measurements for 56 participants were summarized by mean and mode and compared with the subjective reports, using weighted kappa and delta. Results: Data collected from the questionnaire showed poor agreement with objectively measured sleep, with kappas ranging from −0.19 to 0.14. Conclusions: Our results indicate that sleep questions typically used in epidemiologic studies do not closely correspond with objective measures of sleep as assessed using actigraphy. The findings have implications for studies that have used such sleep questions. A means of appropriately measuring sleep as a risk factor in epidemiologic studies remains to be determined.